A cytotoxic survey on 2‐amino‐1H‐imidazol based synthetic marine sponge alkaloid analogues. Issue 8 (2nd November 2022) - Gémes, Nikolett; Makra, Zsófia; Neuperger, Patrícia; Szabó, Enikő; Balog, József Á.; Flink, Lili Borbála; Kari, Beáta; Hackler, László; Puskás, László. G.; Kanizsai, Iván; Szebeni, Gábor J.
Abstract: Here, we describe the synthesis and biologic activity evaluation of 20 novel synthetic marine sponge alkaloid analogues with 2‐amino‐1H‐imidazol (2‐AI) core. Cytotoxicity was tested on murine 4T1 breast cancer, A549 human lung cancer, and HL‐60 human myeloid leukemia cells by the resazurin assay. A total of 18 of 20 compounds showed cytotoxic effect on the cancer cell lines with different potential. Viability of healthy human fibroblasts and peripheral blood mononuclear cells upon treatment was less hampered compared to cancer cell lines supporting tumor cell specific cytotoxicity of our compounds. The most cytotoxic compounds resulted the following IC50 values 28 : 2.91 µM on HL‐60 cells, and 29 : 3.1 µM on 4T1 cells. The A549 cells were less sensitive to the treatments with IC50 15 µM for both 28 and 29 . Flow cytometry demonstrated the apoptotic effect of the most active seven compounds inducing phosphatidylserine exposure and sub‐G1 fragmentation of nuclear DNA. Cell cycle arrest was also observed. Four compounds caused depolarization of the mitochondrial membrane potential as an early event of apoptosis. Two lead compounds inhibited tumor growth in vivo in the 4T1 triple negative breast cancer and A549 human lung adenocarcinoma xenograft models. Novel marine sponge alkaloid analogues are demonstrated as potential anticancer agents for further development.